Use of prophylactic antibiotic therapy in oral surgical procedures: a critical review (2008)
Despite myriad evidence-based data on the efficacy of prophylactic antibiotics in oral surgical procedures, their inaccurate use and indiscriminate abuse still continues in all clinical settings. Although controversy remains, clear-cut guidelines relying on established scientific principles do exist and must be followed. This paper provides a critical and systematic review of each principle and encourages practitioners fit to what current evidence demands.